CHRONIC INFLAMMATION OF THE SCHNEIDERIAN MEMBRANE OF PATIENTS WITH STOMATOGENICAL MAXILLARY SINUSITIS ACCORDING TO THE RESULTS THE DATA OF THE LECTIN HISTOCHEMISTRY - Varzhapetian, S.D.; Gulyuk, A.G.; Barannik, N.G.; Strogonova, T.V. (World of Medicine and Biology, 2018)
The differences of carbohydrate residues distribution in structures of the Schneiderian membrane of different groups was reliable between group of odontogenic maxillary sinusitis and the traumatic form of iatrogenic maxillary sinusitis. The differences of carbohydrate residues between the structures of the Schneiderian membrane was reliable in the group of odontogenic maxillary sinusitis and in the group of medicamentous form of iatrogenic maxillary sinusitis. The differences between saturation of the normal “lamina propria” of Schneiderian membrane and changed with fibrosis are reliable in the group of odontogenic maxillary sinusitis and in the group of medicamentous form of iatrogenic maxillary sinusitis. Distribution of carbohydrate residues differs in different groups of iatrogenic maxillary sinusitis.